Food preference of the giant mudskipper Periophthalmodon schlosseri (Teleostei: Gobiidae). - Zulkifli, Syaizwan Zahmir; Mohamat Yusuff, Ferdaus; Ismail , Ahmad; Miyazaki, Nobuyuki (EDP Sciences, 2012)
The giant mudskipper (Periophthalmodon schlosseri) is one of the commonly found mudskipper species living and it makes a significant biomass value in the mangrove ecosystem. Samples of this mudskipper species were collected and analysed for stomach content and stable isotope ratios (δ13C and δ15N) to determine their food preference. The stomach content analysis showed four groups of food items: fiddler crabs (Uca sp.), medaka fish (Oryzias sp.), juveniles of indeterminate fish species and indeterminate remains of prey items. P. schlosseri females prefer to prey on Oryzias sp. (57.8%), Uca sp. (26.7%) and juveniles of indeterminate fish species (6.7%), while the males prefer to prey on Uca sp. (84.6%) and Oryzias sp. (7.7%). The indeterminate remaining prey items were 8.9% and 7.7% for respective sexes. The stable isotope analysis showed Uca sp. and Oryzias sp. being the main food items for P. schlosseri. The values of δ13C and δ15N ratios also showed differences in food preference among sexes, where females of all life stages prefer to prey more on Oryzias sp. and little Uca sp. In contrast, the male P. schlosseri prefer to prey only on Uca sp. throughout their life, with the exception of juvenile male P. schlosseri, which suggested they also consume a small amount of Oryzias sp. Behavioural differences among the sexes and life stages were suggested to cause differences in food selection. The size of the food items also influences food preference.